Sírios e Libaneses no Sul do Espírito Santo (1890-1930) - Santos, Adilson Silva (2019)
The theme of this thesis is the Syrian and Lebanese immigration in three places in the south of the Espírito Santo state (Itapemirim, Mimoso and Cachoeiro de Itapemirim) between the years 1890 and 1930. The main research problematic is about the reasons t